Characterization of diurnal variations of PM2.5 acidity using an open thermodynamic system: A case study of Guangzhou, China. (July 2018) - Jia, Shiguo; Sarkar, Sayantan; Zhang, Qi; Wang, Xuemei; Wu, Luolin; Chen, Weihua; Huang, Minjuan; Zhou, Shengzhen; Zhang, Jinpu; Yuan, Luan; Yang, Liming
Abstract: Aerosol acidity has significant implications for atmospheric processing, and high time-resolution measurements can provide critical insights into those processes. This paper reports diurnal variations of aerosol acidity characterized using an open thermodynamic system in Guangzhou, China. Hourly measurements of PM2.5 -associated ionic species and related parameters were carried out during June–September 2013 followed by application of the Extended Aerosol Inorganic Model in open mode to estimate aerosol pH. The model-estimated aerosol pH was 2.4 ± 0.3, and the pH diurnal profile exhibited peaks in the early morning (6 a.m.) and troughs in the afternoon (2 p.m.) that appeared to be constrained by liquid water content (LWC) and free H + . A linear regression model was developed to predict aerosol pH, which performed strongly with 4 variables during daytime (NH4 +, Na +, SO4 2− and RH; R 2 = 0.95) and 3 during nighttime (NH4 +, SO4 2− and RH; R 2 = 0.91). The effect of aerosol acidity on the partitioning of HNO3, HCl and NH3 was studied based on theoretical considerations and measurement data. The fractions in particulate phase for acidic compounds correlated strongly with pH (R 2 = 0.64–0.69) while that for NH3, interestingly, was weak (R 2 = 0.17). Analytical expressions were developed to explain these observations and it was concluded that the partitioning of HCl and HNO3 was more sensitive to pH compared to that of NH3 . These results are significant in terms of potential atmospheric depletion rates of HCl and HNO3 in the region and stress the need for future studies in this direction. Graphical abstract: Image 1 Highlights: Diurnal variations of aerosol acidity were analyzed using an open thermodynamic system in a industrialized area in China. The partitioning of HCl and HNO3 was more sensitive to pH compared to that for NH3 . An empirical equation was established to estimate pH of aerosol with satisfactory performance.